Validitas data curah hujan produk satelit IMERG terhadap data curah hujan terukur di wilayah Bima dan Dompu - Rostihanji; Humairo Saidah (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
Complete rainfall data for an extended period is needed to facilitate hydrological analysis. However, there are many obstacles to obtaining the measurement rainfall data as a limitation of rain gauges, especially in remote areas. This study aims to determine the accuracy of rainfall data estimated by the IMERG (Integrated Multi-satellitE Retrievals for GPM) satellite and obtain a correction factor to improve its compatibility with measured rainfall data. The IMERG satellite rain data was corrected using the regression method and the average ratio. The accuracy of the IMERG satellite rain data against the measured rain data is measured from the NSE, R, RMSE, and RB values. The analysis results show that the accuracy of the GPM satellite daily rain data is very low but improving for the ten-daily and monthly periods. Generally, the best correction factors for daily, ten-daily, and monthly periods are obtained using simple linear regression methods and 2nd-order polynomials. The corrected IMERG satellite rain data increase in accuracy, where the monthly rainfall data performs well, the ten-daily data generally complies, and the daily data has not shown good performance. The average values of NSE, R, RMSE, and RB for daily data are 0.14 (poor), 0.37 (weak), 9.18 mm, and -0.12%, respectively; for ten-daily data respectively, 0.40 (fair), 0.63 (strong), 39.42 mm, and 1.47%; and for monthly data are 0.55 (fair), 0.74 (strong), 80.19 mm, and -0.07%. The ten-daily and monthly rainfall data from the IMERG satellite can be used as a rain source data alternative in the Bima and Dompu areas by applying a correction factor.